Manager letters: voluntary disclosure in response to the COVID-19 pandemic - Liu, Lu (Nanyang Technological University, 2023)
I study a novel and popular type of voluntary disclosure: manager letters. Since early 2020, about 50% of S&P 500 firms have issued letters in response to the COVID-19 pandemic. I hand-collect a sample of the letters, and study their contents, linguistic features, determinants, and informativeness. I find that the issuance of the letter is positively related to investors' information demand. Issuing firms experience negative market reactions and downward forecast revisions, and their managers tend to discuss COVID-19 risks in subsequent earning calls, compared to non-issuing firms. However, issuing firms enjoy lower subsequent crash risk. Overall, my results suggest that firms use manager letters to inform investors their exposure to the pandemic. While the disclosure reduces the market's earnings expectations, it helps to minimize the firm's long-term crash risk.